Chapter The King Tutḫaliya IV, the Eflatunpınar Monument, and the River of the Watery Abyss - Balza, Maria Elena (Firenze University Press, 2023)
In recent years, several studies have focused on the interpretation and possible function of the so-called Hittite landscape monuments. For many of these monuments, a connection with the sphere of religion and cultic celebration has been suggested, especially taking into account the possible sanctity of their location, often connected to mountains, rocky outcrops, and water. The landscape monuments would in this sense represent a form of immaterial appropriation of the landscape by the Hittite king, the elites, or, in some cases, local rulers, and would play a specific role in the transmission of messages aimed at consolidating identity and/or spreading consensus. This contribution aims to provide further elements of discussion on the subject, and particularly on the use of landscape monuments as the scene of public events, through a (re)examination of some characteristics of the so-called sacred pool of Eflatunpınar, its possible connection with cult celebrations, and the identity of the ruler that sponsored its construction.